Development and Evaluation of a Training System to Reduce Sensory Conflict Using Augmented Reality - Miyao, Masaru; Takada, Hiroki; Ito, Kikuo; Shiozawa, Tomoki; Takada, Masumi (DESCENTE SPORTS SCIENCE, 2022)
Walking is well known as an aerobic exercise to prevent from the health risk involved in the lifestyle diseases. Indoor training using a treadmill or ergometer can be mentioned as a substitute for outdoor walking. However, a sensory conﬂict between the vestibular and visual systems may be occurred, which induced symptoms of the motion sickness. In addition, virtual reality（VR） can be used to give subjects a sense of realism in outdoor walking. The aim of this study is to develop a VR system that reduces the sensory conﬂict, and to evaluate it with use of bio-signal. As a result, we obtained knowledge involved in the VR video clips that could reduce the sensory conﬂict.